Role of ICT Self-Efficacy and TPACK in Linking AI Literacy to Digital Transformation - Sourav Choudhury; Samiul Biswas; Joy Prakash Deb; Adrija Chattopadhyay; Anukampa Devi; Angita Sarmah Boruah (CV FOUNDAE, 2026)
Rapid technological advancements have positioned digital transformation (DT) as a critical requirement in higher education. However, the mechanisms through which teachers’ artificial intelligence literacy (AIL) contributes to DT remain underexplored, particularly in relation to psychological and pedagogical competencies. This study aims to examine the relationship between AIL and DT among college teachers, with a focus on the mediating roles of ICT self-efficacy (ICTSE) and Technological Pedagogical Content Knowledge (TPACK). A quantitative cross-sectional design was employed using data from 400 college and university teachers across four states in India. Data were analyzed using mediation analysis to test both parallel and serial mediation effects. The findings revealed that AIL is positively associated with DT, both directly and indirectly through ICTSE and TPACK. Both mediators were found to play significant roles, with TPACK demonstrating a stronger mediating effect. Additionally, a significant sequential pathway (AIL → ICTSE → TPACK → DT) was identified, indicating a developmental mechanism linking AI literacy to digital transformation. These findings highlight the importance of enhancing both technological confidence and pedagogical competence to effectively translate AI literacy into transformative educational practices. The study offers important implications for policy and capacity-building initiatives in higher education.